FORMULASI DAN EVALUASI STABILITAS FISIK SUSPENSI IBUPROFEN DENGAN MENGGUNAKAN NATROSOL HBr SEBAGAI BAHAN PENSUSPENSI - Emilia -; Wintari TAURINA; Andhi FAHRURROJI (Media Farmasi Indonesia, 2013)
Ibuprofen it a non-steroidal anti-inflammatory drug which is practically insoluble in water it can be made in the form of suspension. Suspension requires suspending agent such as natrosol HBR for increasing the viscosity and reducing the rate of sedimentation that can produce stable suspension. The aimed of this research is to find the influence of natrosol HBR as the suspending agent toward physical stability of suspension. The method used in the manufacture of ibuprofen suspension is dispersion method. Ibuprofen suspensions were made with variation concentrations of 1%; 1.5%; 2% natrosol HBR respectively. In order to know the physical stability of suspension, it should be carried out organoleptic, density test, particle size distribution, viscosity test, sedimentation volume, redispersibility and pH test. The test result for three formulation suspensions for 30 days storage showed that the physical stablility changed in various showed concentration of natrosol. This research shown that the formulation with concentration of Natrosol Hbr 1% showed the best physical stability of the three formulas which indicated by the required results of the density test, sedimentation volume and redispersibility as well as the best particle size distribution and viscosity of the three formulas ibuprofen suspensions.